2017
DOI: 10.1002/wdev.263
|View full text |Cite
|
Sign up to set email alerts
|

Rare syndromes of the head and face: mandibulofacial and acrofacial dysostoses

Abstract: Craniofacial anomalies account for approximately one-third of all congenital birth defects reflecting the complexity of head and facial development. Craniofacial development is dependent upon a multipotent, migratory population of neural crest cells, which generate most of the bone and cartilage of the head and face. In this review, we discuss advances in our understanding of the pathogenesis of a specific array of craniofacial anomalies, termed facial dysostoses, which can be subdivided into mandibulofacial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 91 publications
1
40
0
2
Order By: Relevance
“…As discussed above, recent studies have revealed that mutations in genes encoding components essential for cell metabolism, such as splicing and ribosome biogenesis, lead to congenital anomalies in craniofacial and limb structure (spliceosomopathies and ribosomopathies,). Developmental etiologies of this kind of craniofacial defects in humans have begun to be unveiled.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, recent studies have revealed that mutations in genes encoding components essential for cell metabolism, such as splicing and ribosome biogenesis, lead to congenital anomalies in craniofacial and limb structure (spliceosomopathies and ribosomopathies,). Developmental etiologies of this kind of craniofacial defects in humans have begun to be unveiled.…”
Section: Discussionmentioning
confidence: 99%
“…3 | TREACHER COLLINS SYNDROME Treacher Collins syndrome (TCS) presents with a wide spectrum of craniofacial defects, often including CA (Andrade et al, 2005;Horiuchi et al, 2004;Trainor, 2010). Mutations in TCOF1, POLR1C and POLR1D are responsible for causing TCS, and all three genes play roles in ribosomal RNA production and subsequently ribosome biogenesis (Terrazas, Dixon, Trainor, & Dixon, 2017;Valdez, Henning, So, Dixon, & Dixon, 2004). The fact that other similar disorders caused by gene mutations that also affect ribosome biogenesis, such as Diamond-Blackfan anemia (Handler, Alabi, & Miller, 2009) or Acrofacial dysotosis (Weaver et al, 2015) can also present with CA suggests that the process of ribosomal biogenesis is critical in the progenitor cells of craniofacial tissues for connecting the nasal airway to the nasopharynx.…”
Section: Neurocristopathymentioning
confidence: 99%
“…TCS is characterized by midfacial hypoplasia, micrognathia with or without cleft palate, underdeveloped external ears and inner ear anomalies with hearing loss, coloboma, and downward slanting eyes (Terrazas, Dixon, Trainor, & Dixon, ). TCS is caused predominantly by mutations in TCOF1 , with mutations in POLR1D and POLR1C associated with some TCOF1 mutation‐negative cases (Terrazas et al, ). TCOF1 is a nucleolar phosphoprotein implicated in Pol I transcription of rRNA (Larsen et al, ).…”
Section: Developmental Processes Linking Spliceosomopathies and Ribosmentioning
confidence: 99%